Eragon - Paolini, Christopher; Paolini, Christopher (New York : Alfred A. Knopf, 2003)
In Aagaesia, a fifteen-year-old boy of unknown lineage named Eragon, finds a mysterious stone that eventually leads to his adoption by the Ingeitum clan who send him to Ellesméra for further training in the vital skills needed to help the Varden in their struggle against the Empire.
Keywords: Fantasy; Adventure and adventurers -- Fiction; Dragons -- Fiction; Magic -- Fiction; Youths' writings; Fiction